2017
DOI: 10.18203/2394-6040.ijcmph20171301
|View full text |Cite
|
Sign up to set email alerts
|

Traditional practices during pregnancy and childbirth among tribal women from Maharashtra: a review

Abstract: There are various traditional beliefs and practices exist in relation to pregnancy and childbirth among various tribal communities in Maharashtra. A review of published literature has conducted and a total of 114 articles and reports were reviewed out of which 14 articles and reports were eligible for the final review. Utilization of maternal and child health (MCH) services during pregnancy and delivery period was reportedly poor among tribal communities due to strong traditional beliefs and trust in Dai, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 6 publications
0
11
0
Order By: Relevance
“…Good communication and liaison between ASHA and ANM workers helped to improve maternal health services in the rural areas, especially improving access to services among marginalized populations [29,30]. Congruent to other studies, we found that women had certain beliefs or customs, related to antenatal check-ups or maternal care, and vaccine hesitancy in certain places [31,32]. These customs or beliefs are passed down from one generation to the other.…”
Section: Discussionmentioning
confidence: 61%
“…Good communication and liaison between ASHA and ANM workers helped to improve maternal health services in the rural areas, especially improving access to services among marginalized populations [29,30]. Congruent to other studies, we found that women had certain beliefs or customs, related to antenatal check-ups or maternal care, and vaccine hesitancy in certain places [31,32]. These customs or beliefs are passed down from one generation to the other.…”
Section: Discussionmentioning
confidence: 61%
“…Among the Bhil tribal community of Gujarat, skin-to-skin care is not a common practice. [ 21 ] A qualitative study (as cited by Begum[ 22 ]) conducted among 30 tribal women from two tribal villages at Ahmednagar reported that the newborns used to be wrapped with cotton clothes. Both the newborn and mother were made to lie down near the place where firewood was burnt to maintain temperature.…”
Section: Discussionmentioning
confidence: 99%
“…Same as in King Sabata Dalindyebo Sub-district, the strong traditional beliefs and practices found in Maharashtra led to the poor utilization of maternal and child health services during pregnancy and delivery, resulting in late prenatal bookings. Such poor maternal and child care services often lead to unhygienic cord care practices, which can cause tetanus and septicaemia to the baby; delay in initiation of breastfeeding involved depriving the new-born of very nutritious and essential colostrum [ 45 ].…”
Section: Discussionmentioning
confidence: 99%